A Synchronous Scheduling Service for Distributed Real-Time Java - Basanta-Val, P.; Estevez-Ayres, I.; Garcia-Valls, M.; Almeida, L. (IEEE transactions on parallel and distributed systems, 2010)
Current trends in real-time systems identify Java as a new alternative to develop both centralized and distributed real-time systems. Many efforts have been devoted to develop the Real-Time Specification for Java (RTSJ), and there is substantial ongoing activity to produce a straightforward and valuable Distributed Real-Time Specification for Java (DRTSJ). The current paper provides a contribution to this latter activity defining, from different angles, a synchronous scheduling service aligned with principles of some popular real-time architectures. This service orchestrates the system in such a way that it provides end-to-end guarantees in the distributed transactions, guaranteeing their timely execution across the network and nodes. The service is described from two points of view: the system one, characterizing a portable model; and the programmer one, defining a distributed object-oriented implementation of a model based on Real-Time Remote Method Invocation (RTRMI). Finally, it also presents results of an implementation carried out to judge the efficiency of the service, offering a preliminary predictability and performance assessment of a distributed real-time Java technology.